IMPLEMENTASI KEBIJAKAN PERATURAN MAHKAMAH AGUNG NOMOR I TAHUN 2008 TENTANG PROSEDUR MEDIASI DI PENGADILAN AGAMA BANDUNG KELAS I.A - Budianto, Kun (Nurani, 2018)
This article discussed regulatory policy on mediation in religious courts way dispute resolution through mediation according to Islamic law and implementation of mediation in settlement court cases in Religious Courts Bandung Class I A. This research base on the policy rules by mediation in the Religious Courts; (a) the benefits to be gained if mediation used as a means in the settlement of disputes, namely the mediation process could overcome the problem of accumulation of matter, the mediation process is viewed as a means of dispute resolution that is faster and cheaper than the litigation process, enforcement of mediation can expand access for all parties to gain a sense of justice, (b) provision their peace efforts in legislation. (c) Indonesian society is a society that likes peace. The Implementation of the mediation process done with two ways, namely mediation initial litigation, and over litigation.